(untitled) (Research, Society and Development, 2020)
First aid is defined by the provision of immediate support for the purpose of maintaining the victim’s vital signs until the arrival of specialized assistance. In addition to health professionals, any individual with prior knowledge of the subject can provide the help. This research aimed to know the importance of the knowledge of elementary school teachers about first aid. This is a descriptive research, exploratory and with a qualitative approach. The study was 15 teachers from three public elementary schools located in the interior of Ceará, who were teaching in public elementary schools. Data were collected from November 2019 to March 2020, from the application of a semi-structured questionnaire. The results showed that there is a lack of information about educators’ understanding of first aid theory and practices, as well as the use of popular practices that can aggravate the patient’s condition. Therefore, actions and strategies to promote continuing training for education professionals on the provision of relief should be implemented. To this way, ensure a better guideline for the prevention of accidents, injuries and health care.